Arte americano : contextos y formas de ver : Terceras Jornadas de Historia del Arte - Martínez Silva, Juan Manuel (RiL Editores, 2006)
Papers presented during the 3rd Meeting of Art History celebrated in Valparaiso in 2006 and where for the first time Pre-Columbian art was included as one of the main categories. The central topic of this edition was dedicated to the spectator and the perception of art with papers centered in the analysis of morphological and iconographic elements to reconstruct how artwork was perceived in the past and the multiple views of the present. Presentations are divided into the follwing catelgories: Arte Precolombino; Arte Virreinal; Arte en el siglo XIX; Arte contemporáneo.